2023
DOI: 10.1038/s41598-023-36690-4
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth release from endodontic materials: in vivo analysis using Wistar rats

Abstract: Calcium silicate-based materials are used to block the communication between the root canal and the periodontal ligament space. This brings the materials into contact with tissues and the potential for local and systemic elemental release and movement. The aim of the study was to evaluate the elemental release of bismuth from ProRoot MTA in contact with connective tissues after 30 and 180 days as well as any accumulation in peripheral organs using an animal model. Tricalcium silicate and hydroxyapatite contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Zirconium dioxide, Bismuth oxide or Tantalum pentoxide) and their release from periapical extrusion into the body fluids must be considered in future research. Recent ex vivo studies showed that, upon dissolution of CaSi sealers samples, the radiopacifiers could be spread in the surgical area, taken up by cells and transferred to other organs for their elimination by metabolic processes (de Azevedo Queiroz et al., 2021; Marciano et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Zirconium dioxide, Bismuth oxide or Tantalum pentoxide) and their release from periapical extrusion into the body fluids must be considered in future research. Recent ex vivo studies showed that, upon dissolution of CaSi sealers samples, the radiopacifiers could be spread in the surgical area, taken up by cells and transferred to other organs for their elimination by metabolic processes (de Azevedo Queiroz et al., 2021; Marciano et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of bismuth in previous cell culture studies induced an upregulation of metallothionein (a cysteine-rich protein involved in metal detoxification) expression (Cowan et al, 1996;Durnam and Palmiter, 1987;Kagimoto et al, 1991;Kaji et al, 1996), as bismuth compounds strong agonists for metallothionein. The research that has been undertaken aims to guide the dental clinician to select a bismuth-free calcium silicatebased material since bismuth oxide causes dentine discolouration, can migrate from the material to connective subcutaneous tissue (Schembri Wismayer et al, 2016) and bone (Marciano et al, 2023) and it can accumulate in peripheral organs (mainly kidneys) following implantation (Marciano et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to bismuth oxide, the radioopacifier in MTA. Previous studies have shown the long-term release of bismuth oxide into the neighboring tissues and its interaction with other substances, which could potentially explain its influence on the release of growth factors in conditioned media [ 45 , 46 ]. A time course of growth factor release during a seven-day period could probably enable a better understanding of the effects of long-term exposure to an alkaline environment.…”
Section: Discussionmentioning
confidence: 99%